Two lines of defense in the pupas of ichneumonid wasp parasitoids associated with spider hosts - Korenko, Stanislav; Sýkora, Jakub; Kostro-Ambroziak, Agata; Pekár, Stano (Frontiers in Ecology and Evolution, 2022)
Insects in the pupal stage are vulnerable to various predators because the pupa is immobile. The pupas of parasitoid ichneumonid wasps (Ichneumonidae) associated with spider hosts have evolved two lines of defense against predators, namely a cocoon spun by the parasitoid larva and a web provided by the spider host. The web is derived from a normal or modified spider web built by the spider under manipulation by the penultimate instar of the parasitoid wasp. In laboratory experiments, we tested the efficacy of these two defensive lines using six potential predators with two different types of mouthparts coming from three foraging guilds. The presence of the cocoon significantly reduced predation. Scavengers with chewing mouthparts, e.g., cockroaches and crickets, attacked and consumed pupas within both sparse and strong cocoon walls. Scavengers with piercing mouthparts were able to attack pupas in cocoons with a sparse wall, but not with a strong wall. Collectors and true predators showed no interest in cocoons. The presence of a web increased pupa protection by up to 80% when the web was on the ground and by up to 95% when the web was in the air. Only scavengers with chewing mouthparts were able to reach and consume pupas sheltered by the web. We provide the first evidence of how the two lines of defense contribute to parasitoid defense during the pupal stage.